THEME AND THEMATIC PROGRESSION ANALYSIS OF ANALYTICAL EXPOSITION TEXTS - Sianipar, Rafita Tioria (2015)
As part of the bigger study conducted by Emilia, et al. (2014) on the implementation of Genre Based Approach (GBA) in teaching writing in tertiary context (see also Emilia, 2011), this study focuses on investigating the realization of the Theme and the thematic progression in students' analytical exposition texts in a state university in Bandung. This study also intends to find out the contribution of the Theme and thematic progression on the nature of the students' analytical exposition texts. To fulfill its objectives, this study employs a descriptive-qualitative research design embracing the characteristics of a case study approach. The data are obtained from the collection of students' analytical exposition texts. This study uses the theory of Theme system developed by Halliday (1994), Eggins (1994; 2004) and the theory of thematic progression proposed by Eggins (1994; 2004 as the framework to analyze the data. This study reveals that the there are three types of Theme realized in students' writings: Topical Theme, Interpersonal Theme, and Textual Theme, and there are also three types of thematic progression pattern applied in students' texts: Theme Reiteration pattern, Zig Zag pattern, and Multiple Theme pattern. The findings also suggest that the Theme and thematic progression support the nature of the analytical exposition texts written by the students to some extent: the Topical Theme represents the generalized participants in the texts, the Interpersonal Theme helps students stating their positions, while the Textual Theme provides cohesion and coherence and also connects steps in arguments in the students' texts. In terms of thematic progression patterns, the Multiple Theme pattern gives signposts for the arguments in the text level, the Theme Reiteration helps students maintain the focus of the arguments in the clause level, and the Zig Zag pattern reinforces the arguments also in the clause level, particularly in relation of causality, in the students' analytical exposition texts. In terms of the structure, the texts written by the students has met the nature of analytical exposition text. This study, as part of the bigger study on GBA, indicates that GBA can lead students to write good analytical exposition texts. Therefore, it is recommended that GBA is implemented in the teaching-learning process, and that the Theme and thematic progression is taught explicitly at educational settings.